Brasilian medium-sized cities’ configurational patterns: similarities and differences. - Côrtes Bogniotti, Glaucia Maria (2022)
This paper focuses on evaluating Brazilian mid-sized cities and how their morphological attributes, expressed by centrality and accessibility of the transportation infrastructure, interact with its population, implying limitations and potentials for improvements in the urban network. The sample is composed by nine Brazilian cities investigated by the ReCiMe: Uberlândia/MG, Londrina/PR, Passo Fundo/RS, Chapecó/SC, Dourados/MS, Marília/SP, Marabá/PA, Campina Grande/PB and Mossoró/RN. These municipalities are distributed across the country, in several states, and to some extent represent the diversity of the national urban scenario. The theoretical, methodological, and technical approach is based on Space Syntax strategies associated with non-configurational variables, including geopolitical, economical, and socio-spatial data made available by ReCiMe. The study database was structured in a Geographic Information System and cities were explored comparatively, according to the present-day panorama and the historical one, in a diachronic perspective: axial and segment maps were developed since the foundation data up to 2017. Findings suggest these cities present a clear social and spatial inequality pattern that fragments the urban systems and promotes a general sensation of public unsafety. There is a highlighted distance among the social stratum, creating an ambiguous scenario of richness and poverty, representing, to some extent, the Brazilian social conflict. The findings point to the existence of, if not to a type at least a similar pattern of socioeconomic structure, urban expansion process, and socio-spatial inequality.